Interleukin-1β-induced IRAK1 ubiquitination is required for TH-GM-CSF cell differentiation in T cell-mediated inflammation. (August 2019) - Hu, Yuan; Xu, Feihong; Zhang, Ruihua; Legarda, Diana; Dai, Jun; Wang, Di; Li, Heyu; Zhang, Yao; Xue, Qingjie; Dong, Guanjun; Zhang, Hui; Lu, Chang; et al.
Abstract: Accumulating evidence suggests granulocyte macrophage-colony stimulating factor (GM-CSF) can function as an inflammatory mediator, but whether GM-CSF-producing CD4 + T cells (TH -GM-CSF) are a distinct T helper cell subset is lacking. Herein we demonstrate that interleukin (IL)-1β exclusively drives differentiation of naïve CD4 + T cells into TH -GM-CSF cells via inducing ubiquitination of IL-1 receptor-associated kinase 1 (IRAK1) and subsequent activation of the transcription factor NF-kappaB (NF-κB), independent of RAR-related orphan receptor gamma (RORγt) required for TH 17 differentiation. In vivo, TH -GM-CSF cells are present in murine Citrobacter Rodentium infections and mediate colitis following adoptive transfer of CD4 + T cells into Rag1 −/− mice via GM-CSF-induced macrophage activation. The TH -GM-CSF cell phenotype is stable and distinct from the TH 17 genetic program, but IL-1β can convert pre-formed TH 17 cells into TH -GM-CSF cells, thereby accounting for previously reported associations between IL-17 and GM-CSF. Together, our results newly identify IL-1β/NF-κB-dependent TH -GM-CSF cells as a unique T helper cell subset and highlight the importance of CD4 + T cell-derived GM-CSF induced macrophage activation as a previously undescribed T cell effector mechanism. Highlights: Our study newly identifies GM-‐CSF-‐single producing T helper cells (TH-‐GM-‐CSF) as a unique T helper subset. Our study reveals that IL-‐1® directly programs TH-‐GM-‐CSF differentiation via IRAK1/NF-‐κB axis and that IL-‐1® induces conversion of TH17 into TH-‐GM-‐CSF. Our study shows that TH-‐GM-‐CSF cells are critically involved in the development of T cell transfer induced colitis. These novel findings will lead to more exciting investigations concerning the contributions of TH-‐GM-‐CSF in various T cell-‐ mediated inflammatory diseases.